Шляхи підвищення надійності і довговічності шнекових механізмів машин - Гупка, Б. В. (Видавництво Національного університету «Львівська політехніка», 2001)
A number of design and technological measures for raising wear-resistance of working elements of screw-conveyer mechanisms is suggested. The constructions of stands for comparative study and given.